Relationship of maternal serum vitamin D level with preeclampsia - Eva, Nusrat Jahan; Jahan, Muna Shalima; Ahmed, Naorin; Khan, Farzana Farhin; Nesa, M. Karimatun; Nahar, M. Irin; Islam, M. Tariqul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Vitamin D deficiency has been increasingly implicated in adverse pregnancy outcomes, including preeclampsia; however, evidence from South Asian populations remains limited. This study aimed to evaluate the relationship between maternal serum vitamin D levels and preeclampsia in pregnant women in Bangladesh. Methods: A hospital-based case-control study was conducted at Sir Salimullah Medical College Mitford Hospital in Dhaka from March 2019 to March 2020. A total of 106 pregnant women aged 18–35 years with gestational age 28-40 weeks were enrolled, 53 with preeclampsia and 53 normotensive controls. Data on sociodemographic and obstetric characteristics were collected through interviews. Serum 25(OH)D concentrations were measured using chemiluminescence immunoassay and categorized as deficient (≤20 ng/ml), insufficient (21-29 ng/ml), and sufficient (≥30 ng/ml). Statistical analyses were performed using SPSS version 23.0, and p<0.05 was considered significant. Results: Mean serum vitamin D levels were significantly lower in preeclamptic women (13.41±6.83 ng/ml) than in controls (19.96±9.07 ng/ml, p<0.001). Women with vitamin D levels <30 ng/ml had 7.46 times greater odds of developing preeclampsia (95% CI 1.58-35.25). In the multivariate analysis, both deficient and insufficient vitamin D levels remained significant predictors (OR = 6.03 and 6.55, respectively). Conclusions: Low maternal serum vitamin D levels were strongly associated with preeclampsia. Routine screening and adequate vitamin D supplementation during pregnancy may help reduce the risk of this potentially fatal disorder.